ENVIRONMENTAL CONTAMINATION, DNA DAMAGE AND MECHANISM OF CYTOGENOTOXICITY INDUCED BY ELECTRONIC WASTES IN LAGOS, NIGERIA (2013)
Indiscriminate disposal of electronic wastes (e-wastes) in Nigeria is on the increase. The release of hazardous substances from these wastes may have harmful consequences on the environment and public health. In Nigeria, there is dearth of information on environmental contamination and genotoxicity of e-wastes, and the mechanism of genetic damage. This study was designed to investigate the level of contaminants in soil, plant and well water; potential in vivo and in vitro cytogenotoxicity and mechanism of DNA damage induced by e-wastes in Lagos, Nigeria. Dumpsites from two major electronic markets, Alaba International (AI) and Computer Village (CV), in Lagos were purposely selected. Sixteen USEPA priority Polyaromatic Hydrocarbons (PAHs), 28 WHO toxic Polychlorinated Biphenyls (PCBs), and 8 carcinogenic Polybrominated Diphenyl Ethers (PBDEs) were analysed in the dumpsites’ Soils (AIS, CVS) collected at depth 0 – 10 cm, and Plant (Amaranthus hybridus; AIP, CVP) using gas chromatography-mass spectrophotometry. Lead, cadmium and copper concentrations in the soils, A. hybridus and Well Water (AIWW, CVWW) collected from the dumpsite vicinity were measured using atomic absorption spectrophotometry. Genotoxicity was carried out with the e-wastes Leachate (AIL, CVL) at different concentrations (0-50 %) and well water using the micronucleus and sperm morphology assays in mice, and in vitro, using the alkaline comet assay in human peripheral blood lymphocytes. The oxidative stress in mice exposed to AIL and AIWW was assessed using biochemical parameters [Catalase, reduced Glutathione (GSH), and Alanine Aminotransferase (ALT)] according to standard methods. The NIH/3T3 mouse fibroblast cell line exposed to AIL was used to assess cytotoxicity using 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and the cell cycle using flow cytometry technique. The Mitochondrial Membrane Potential (MMP) of the cell line was evaluated using JC-1 probe. Data were analysed using descriptive statistics and ANOVA at p=0.05. The total PAHs (mg/kg), PCBs (µg/kg) and PBDEs were AIS=116.5, CVS=95.4, AIP=14.9, CVP=6.2; AIS=4063, CVS=3619, AIP=889, CVP=518 and AIS=34.7 mg/kg, CVS=13.3 mg/kg, AIP=31.1 µg/kg, CVP=11.5 µg/kg respectively. The metal (lead, cadmium and copper) concentrations (mg/L) respectively in the leachate (397.0-867.5, 12.1-18.0, 14.3-22.3), A. hybridus (12.8-23.3, 0.3-0.8, 1.0-1.6) and well water (0.1-0.4, 0.1-0.7, 0.001-0.7) were above NESREA and WHO limits. There was a concentration-dependent, significant induction of micronucleated polychromatic erythrocytes (AIL=9.3±0.9-24.5±1.3, CVL=9.0±0.8-23.0±0.8; AIWW=8.2±1.2-13.8±1.4, CVWW=8.0±0.4-12.3±0.8) and significant increase in sperm abnormalities (AIL=83.2±2.2-157.6±1.9, CVL=81.0±1.3-155.9±2.0; AIWW=67.9±1.9-88.1±1.4, CVWW=66.5±0.8-86.1±0.8) in mice. In vitro, the leachate induced significant increases in DNA damage (AIL=1.6±0.3-6.9±0.5; CVL=0.9±0.3-4.5±0.5) in human lymphocytes. There was a significant increase in GSH (AIL=8.7±0.1-14.2±0.1, AIWW=8.7±0.1-12.4±0.1 µm/g) and activities of Catalase (AIL=76.3±0.9-134.0±1.4, AIWW=78.0±0.8-96.0±0.8 µm/mg) and ALT (AIL=21.0±0.8-47.0±0.8, AIWW=20.0±0.8-36.8±0.5 U/mL) compared to the negative control. There was increased cell death (IC50=30 %), significant disruption of MMP and induction of apoptosis evident in accumulation of sub/G1 (8.3-72.2 %) stage of the NIH/3T3 cell cycle. Electronic wastes from Alaba international and Computer village market dumpsites contained organic and inorganic toxins that induced cytogenetic damage. Oxidative damage and apoptotic pathway could be the mechanisms of the cytogenotoxicity.